(untitled) - Peck, Roxy (Belmont, CA, 2020)
This 6th Edition contains new sections on randomization-based inference: bootstrap methods for simulation-based confidence intervals and randomization tests of hypotheses. These new sections are accompanied by online Shiny apps, which can be used to construct bootstrap confidence intervals and to carry out randomization tests. In addition, a new visualization tool at statistics.cengage.com will help you understand these new concepts. WebAssign for Statistics accompanies this text. Designed by educators, WebAssign helps you learn not just do homework. WebAssign grants access to the ebook, assessments and analytics to enable you to be a self-sufficient learner and help you succeed in your course.
Keywords: Statistics,Mathematical statistics,Thống kê,Thống kê toán học